2023
DOI: 10.51542/ijscia.v4i1.24
|View full text |Cite
|
Sign up to set email alerts
|

Smoking as A Risk Factor of Low Superoxide Dismutase (SOD) Levels and Early Aging in Women Aged 20 to 35 Years

Abstract: Background: Heavy smokers have four times more facial wrinkles than non-smokers. Superoxide dismutase (SOD) levels are an indicator of premature aging in blood and tissues. The premature aging process can take place more quickly at a relatively younger age. The purpose of this study was to determine smoking and low levels of superoxide dismutase (SOD) as risk factors for premature aging in women aged 20-35 years. Method: Using a case-control study, this study determined smoking and low levels of superoxide dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Linli et al ( 48 ) demonstrated that smoking correlates with accelerated brain aging, influenced by smoking characteristics like duration and intensity. Research by Laksmi et al ( 49 ) stated that smoking and low levels of superoxide dismutase (SOD) are risk factors for premature aging in women. These studies signify the association of nicotine exposure with biological aging, highlighting the necessity to augment awareness regarding this connection.…”
Section: Discussionmentioning
confidence: 99%
“…Linli et al ( 48 ) demonstrated that smoking correlates with accelerated brain aging, influenced by smoking characteristics like duration and intensity. Research by Laksmi et al ( 49 ) stated that smoking and low levels of superoxide dismutase (SOD) are risk factors for premature aging in women. These studies signify the association of nicotine exposure with biological aging, highlighting the necessity to augment awareness regarding this connection.…”
Section: Discussionmentioning
confidence: 99%